Case Report: Rehabilitation for Lower Extremity Pain Due to Venous Stasis in a Patient With Multisystem Inflammatory Syndrome in Children - Kinoshita, Tokio; Nishimura, Yukihide; Umemoto, Yasunori; Koike, Yumi; Kouda, Ken; Ogawa, Takahiro; Suenaga, Tomohiro; Tajima, Fumihiro (Frontiers in Pediatrics, 2022)
Recently, it was reported that children recovering from coronavirus disease developed multisystem inflammatory syndrome in children (MIS-C), which causes severe inflammation in multiple organs of the body. Because MIS-C is a new disease, the pathophysiology and prognosis are unknown. Owing to a lack of studies on this subject, we herein provide information on rehabilitation for children with MIS-C, A 12-year-old male patient presented with systemic inflammatory symptoms after approximately two months since recovery from coronavirus disease. He was treated with cyclosporine and steroid pulse therapy after admission to our hospital. His general condition improved significantly within approximately one week. Thereafter, his lower legs turned dark purple and he experienced intense pain whenever the lower limbs hung below the heart, such as in the sitting position. The patient was referred to the rehabilitation department, as he had difficulties during standing and walking. Because the symptoms improved with elevation of the lower extremities, we considered that the pain was related to venous stasis. The pain reduced when an elastic bandage was applied for the prevention of venous stasis; therefore, exercise therapy was implemented while the patient wore the elastic bandage. The patient's lower extremity symptoms improved in 10 days. He was discharged after 16 days and could independently perform activities of daily living. The mechanism underlying the patient’s pain could not be determined; however, rehabilitation was effective when combined with compression therapy using an elastic bandage.